Controle social: sob condicionantes específicos ao Brasil ou impasse estrutural? - Ribeiro, Agatha Justen Gonçalves (2012)
This paper examines the exercise of social control in Brazil, from the more general context that prompted him, as well as the internal context that led to the creation of institutionalized spaces for your application. Through joint studies by other researchers in Public Policy Management Councils in the three levels of government - local, state and federal - and empirical study, we found that the way the exercise of social control happens in practice, much moves away from what the law provides. Taking, then based on the existing difficulties in the development of social control, the authors sought to interpreters in Brazil, and the theories about the origin and functions of the modern state, possible explanations for this fact. Thus, it is considered that barriers to the development of social control in Brazil if one parties related to characteristics specific to the country, the other is due to the historical dynamics of the capitalist system.